Negotiating Multiple Risks: Health, safety, and well-being among internal migrant sex workers in Brazil during COVID-19 - Martins Jr, Angelo; Brito, Larissa; Scatena, Thiago Pizzo (Anti-Trafficking Review, 2023)
During the COVID-19 pandemic, experts called attention to the fact that the pandemic was disproportionately affecting socially vulnerable groups. Research suggested that structural inequalities resulted in unequal access to healthcare and that infection prevention measures increased precarious working conditions in illegal, informal, or unregulated sectors, such as the sex industry. This article reports on research findings that examined the impact of the COVID-19 pandemic on the lives and working conditions of 25 women internal migrant sex workers in the city of Ribeirão Preto, Brazil. It demonstrates that the pandemic and measures to control it severely impacted the lives of internal migrant sex workers, their affective and work relationships, as well as their income, safety, and physical and mental health. Furthermore, sex workers suffered from disturbing levels of violence and precariousness as well as a lack of effective policies aimed at protecting their health and well-being. This was exacerbated by the stigma, lack of labour rights, and the fact that they were migrants, which impacted them financially and emotionally during movement restrictions.